Spatial Distribution of Polychaeta at Tangerang Coastal Water, Banten Province - Asep Sahidin; Yusli Wardiatno (JURNAL PERIKANAN DAN KELAUTAN, 2016)
Polychaeta is the benthos organisms that have an important role in nutrient cycling, decomposition, mineralization, magnification and caterers to the seabed. This study aimed to determine the density and spatial distribution of Polychaeta in the Coastal of Tangerang, Banten. The research was conducted from April to August 2014 along the coast of Tangerang, Banten. It consists of 52 stations are divided into three different locations (Kronjo, Cituis and Tanjung Pasir). The research found 5454 specimens in 25 species of Polychaeta. The highest density found in the Tanjung Pasir location (151 Ind/m2) followed Kronjo location (105 Ind/m2) and the lowest on the Cituis location (25 Ind/m2). Spatial distribution based on claster Bray-Curtis analysis showing the Kronjo location form one group (76.47%), Cituis up into five groups and Tanjung Pasir form one group (72.6%). Canonical Correspondence Analysis (CCA) relationships distribution of the fraction on sediment with Polychaeta showed Sternapsis scutata, this Polychaeta deposit feeders dominate on the mud substrate and Exogone naidin, Capitella capitata, Scoloplos armiger, Aphrodate aculeate and Glycera capitata. Polychaeta are predators dominate the sand substrate, while Ophryotracha puerilis is cosmopolitan Polychaeta spread at each location and station.Keywords: